Does Oblique Effect Affect SSVEP-Based Visual Acuity Assessment? - Zheng, Xiaowei; Xu, Guanghua; Du, Yuhui; Li, Hui; Han, Chengcheng; Tian, Peiyuan; Li, Zejin; Du, Chenghang; Yan, Wenqiang; Zhang, Sicong (Frontiers in Neuroscience, 2022)
This study aimed to explore that whether there was an effect on SSVEP visual acuity assessment from the oblique effect or the stimulus orientation. SSVEPs were induced by seven visual stimuli, e.g., the reversal sinusoidal gratings with horizontal, two oblique, and vertical orientations, reversal checkerboards with vertical and oblique orientations, and oscillating expansion-contraction concentric-rings, at six spatial frequency steps. Ten subjects participated in the experiment. Subsequently, a threshold estimation criterion was used to determine the objective SSVEP visual acuity corresponding to each visual stimulus. Taking the SSVEP amplitude and SNR of the fundamental reversal frequency as signal characteristics, both the SSVEP amplitude and SNR induced by the reversal sinusoidal gratings at 3.0 cpd among four stimulus orientations had no significant difference, and the same finding was also shown in the checkerboards between vertical and oblique orientation. Besides, the SSVEP visual acuity obtained by the threshold estimation criterion for all seven visual stimuli also showed no significant difference. This study demonstrated that the SSVEPs induced by all these seven visual stimuli had a similarly good performance in evaluating visual acuity, and the oblique effect or the stimulus orientation had little effect on SSVEP response as well as the SSVEP visual acuity.